Kesalahan Penggunaan Tata Bahasa dalam Media Sosial : Pada Kebebasan Ekspresi dan Kaidah Bahasa Indonesia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The development of social media as a public communication space has had a significant impact on language use, particularly grammar. This article discusses the use of grammar on social media, which is often caused by the freedom of expression not being balanced with an awareness of proper and correct language. Through a qualitative approach with discourse analysis, this article highlights how deviations from grammatical rules in social media posts reflect a shift in societal attitudes towards linguistic norms. On one hand, linguistic freedom on social media is considered a form of creativity and self-expression. However, on the other hand, it has the potential to weaken language skills that adhere to rules, especially among the younger generation. This article will certainly provide a recommendation on the importance of language literacy as an effort to maintain the quality of public communication amidst the wave of digitalization and the expanding freedom of expression.